On Convergence of Nourein Iterations for Simultaneous Finding All Zeros of a Polynomial (Journal of Computational Mathematics, 2000)
In this paper, we give the first estimation conditions for Nourein iterations for simultaneous finding all zeros of a polynomial under which the iteration processes are guaranteed to converge.